Respuesta :

Answer:

7 x 3 .

Step-by-step explanation:

Divide x x by 1 1 . Since g(f(x))=x g ( f ( x ) ) = x , f−1(x)=3√49x7 f - 1 ( x ) = 49 x 3 7 is the inverse of f(x)=7x3 f ( x )

The inverse function is y= (x-3)/7

What is a function?

An expression which defines the relationship between two variables (one independent and one dependent variable).

What is dependent and independent variable?

The independent variable is the variable being controlled in the problem, and the dependent variable is the variable that changes with the change of independent variable.

What is inverse of a function?

A function that undoes the original function is called the inverse function.

How to find the inverse of y=7x+3 ?

To find the inverse function of a given function,

  • first we will have to interchange the variables

In the problem,  

  • y is the independent variable
  • x is the dependent variable

y=7x+3

To find the inverse

x = 7y + 3    ( interchanging the variables )

Now finding the value of y,

⇒ x - 3 = 7y

⇒ y = (x-3)/7

This is the inverse function.

Find out more information about inverse function here: https://brainly.com/question/10219387

#SPJ2

Otras preguntas

ACCESS MORE